Poe and the printed word - Hayes, Kevin J. (Cambridge studies in American literature and culture., 2000)
Edgar Allan Poe continues to be a fascinating literary figure to students and scholars alike. Increasingly the focus of study pushes beyond the fright and amusement of his famous tales and seeks to locate the author within the culture of his time. In Poe and the Printed Word, Kevin Hayes explores the relationship between various facets of print culture and Poe's writings. His study provides a fuller picture of Poe's life and works by examining how the publishing opportunities of his time influenced his development as a writer. Hayes demonstrates how Poe employed different methods of publication as a showcase for his verse, criticism and fiction. Beginning with Poe's early exposure to the printed word, and ending with the ambitious magazine and book projects of his final years, this reappraisal of Poe's career provides an engaging account that is part biography, part literary history and part history of the book.